Impact of a short term awareness teaching programme on primary and middle school teachers about the neurological factors that affect learning disability - Iype, Mary; Jayachandran, Nandini; Vinod, Divya; Suresh, Poovathinal Azhakan (Indian Journal of Child Health, 2020)
Background: Needs of children with specific learning disability (SLD) should be noticed and answered in the regular school. Objective: We aimed to find out the knowledge among school teachers about neurological factors that affect SLD. Our secondary objective was to find the effect of short-term teaching on their knowledge. Materials and Methods: We chose an observational study design. A total of 51 teachers of standard 1–7, from a Central board of Secondary Education school, an Indian Certificate of Secondary Education school and a state syllabus school participated. They were grouped as pre-primary, primary, and middle school. The participants were trained at their respective schools. The training program consisted of didactic lectures, case discussions, and group discussions about SLD from a multidisciplinary perspective, spanning over 3 days. A total of two questionnaires were administered to the teachers; one before and one after the 3 days training. Results: The mean scores obtained by the pre-primary teachers before and after training were 3.69 and 5.69, respectively (significant at 1% level of significance). The primary school teachers scored a mean of 3.44 before training and 5.11 after, with statistically significant improvement. In the pre- and post-test scores of middle school teachers (4.29 and 5.35), though improvement in knowledge was seen, it was not statistically significant. Conclusion: The fact that a short-term teaching program for teachers regarding the neurological aspects of SLD was effective, underscores need for regular teaching programs for all teachers. It would be ideal if the knowledge is imparted in the curriculum during basic teacher training so that all answers would be right prior to the in-service training.